Website and pricing strategy development: a business coaching at local SME - Lery Anggityo; Lily Sudhartio (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Small and medium-sized enterprises (SME) make a very large contribution to Indonesia's gross domestic product (GDP) and absorb a lot of labor from the entire workforce. Unfortunately, many SMEs face so many problems in their business operation. Whether the issues arising from internal factors such as management or external factors such as the COVID-19 pandemic, therefore they need support and insights from the experts on how to solve their problems. The current business coaching was conducted in PT Bumi Perkasa Internasional, a small business located in Bekasi, West Java and is engaged in the manufacturing industry with the scope of expertise in the Dust Collector System. The Business Coaching used a qualitative approach that mapping the real conditions and problems of SMEs, then propose solutions, and implement them for SMEs improvement. this method requires two types of data, primary data and secondary data Primary data collection technique is obtained by interview, observation and documentation. Secondary data was obtained by conducting a literature study related to information on the manufacturing industry, SMEs itself, finance, marketing, operations management and human resource management The result shows that the company did not have an effective website as its marketing channel and an unfavorable pricing strategy, indicated by no leads originating from the company's website and inability to profit from the project. The business coaching suggests the management to develop their website and pricing strategy to improve their conditions.